Advances in organic nano-architectures based on NIR-II small-molecule fluorophores for biomedical imaging and therapy - Bian, Hui; Ma, Dandan; Nan, Yi; Kim, Myung Hwa; Kim, Sehoon; Chen, Xiaoqiang; Peng, Xiaojun; Yoon, Juyoung (Elsevier BV, 2025)
The second near-infrared window (NIR-II) has emerged as a highly promising domain for clinical applications, with small-molecule fluorophores leading this development. Various fluorophores, such as cyanine dyes, rhodamines, BODIPY, and D-A structured molecules, have been specifically designed to meet diverse biomedical needs. These fluorophores are distinguished by their precise chemical structures, ease of modification, and excellent biocompatibility, making them ideal for medical applications such as precise fluorescence imaging of micro bio-tissues, surgical navigation, in vivo cell tracking, advanced biosensing, and targeted phototherapy for malignant cell eradication. However, significant challenges persist in the clinical translation of these fluorophores, including low fluorescence efficiency and insufficient targeting specificity for diseased tissues. Nanotechnology has emerged as a powerful strategy to overcome these obstacles. Integrating nanocarriers with fluorophores enhances their photophysical characteristics, such as enhancing fluorescence emission, reactive oxygen species generation, and photothermal conversion efficiency in biological environments. Additionally, nanocarriers improve biophysical properties by enhancing solubility, prolonging circulation times, improving biocompatibility, and enabling more precise accumulation in pathological tissues. This review comprehensively analyzes the fundamental challenges associated with NIR-II small molecules, focusing on limitations that cannot be addressed through simple chemical modifications. It also explores how nanotechnology-based approaches can alleviate these challenges, emphasizing the mechanisms behind these enhancements. Furthermore, the review highlights the broad biomedical applications of nano-engineered NIR-II fluorophores. Lastly, it discusses the remaining barriers to clinical translation and emphasizes the growing role of artificial intelligence in expediting the rational design of novel NIR-II fluorophores and optimizing image processing techniques for enhanced diagnostic precision. By providing a comprehensive overview of the current state of the field, this review provides key insights that could expedite the clinical translation of NIR-II technologies.